Living with voices in childhood: content, influence and reception strategies - de Souza Cardoso, Clarissa (2024)
Identify content, influence and strategies for welcoming the experience based on the narrative of children who hear voices. Method: narrative-qualitative study, Benjaminian concepts of experience and language were used to analyze the contributions of four children, aged between nine and 12 years old, self-declared voice hearers. Results and discussions: they presented friendly voices as content that positively influenced daily life, while voices difficult to deal with induced social distancing. The strategies developed were: Reiki practice, participation in the Group, literary writing, drawing, online games. Final considerations: The contents can include voices, visions, and sensations; the influence is attributed to introspection and insecurity, and one of the strategies was the United Children Group.